An instrument to measure adherence to the Protestant Ethic and contemporary work values - Stanford Wayne, F. (Journal of business ethics, 1989)
The problem of the current research is to develop an instrument that accurately measures individuals' adherence or nonadherence to both Protestant Ethic and contemporary work values. The study confirms that the traditional Protestant Ethic work values and the contemporary work values are different and the instrument used to measure the work values that individuals actually support is valid and reliable. Two scales were developed based on Protestant Ethic work values and contemporary work values. A four-point Likert scale was used to indicate the extent of agreement or disagreement with statements written to represent Protestant Ethic and contemporary work values. Face and content validities of the instrument were established by using two panels of experts — one consisted of authorities in the area of work values; the other consisted of editorial critics. Reliability of the instrument was confirmed by the Kuder-Richardson and test-retest methods. Four sets of work values emerged with significant discrimination among them.